2015
DOI: 10.5901/jesr.2015.v5n1p329
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Perceptions of Parental Punitive Discipline and Involvement in Delinquent Behaviours among Selected Kenyan Secondary School Students

Abstract: The study investigated the relationship between perceptions of parental punitive discipline and involvement in non-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Conversely, Kariuki et al (2015) observed that when behavior modification techniques were applied to handle such students, there was a reduction of maladaptive behaviors of the students irrespective of their gender. On the other hand, Kwaja and Mormah (2011) noted that the use of counselling curriculum in schools, reinforcement, and counselling adolescents in moral values are the most effective strategies for managing maladaptive behaviour.…”
Section: Strategies That Teacher Use To Manage Maladaptive Behaviour Of Studentsmentioning
confidence: 96%
See 1 more Smart Citation
“…Conversely, Kariuki et al (2015) observed that when behavior modification techniques were applied to handle such students, there was a reduction of maladaptive behaviors of the students irrespective of their gender. On the other hand, Kwaja and Mormah (2011) noted that the use of counselling curriculum in schools, reinforcement, and counselling adolescents in moral values are the most effective strategies for managing maladaptive behaviour.…”
Section: Strategies That Teacher Use To Manage Maladaptive Behaviour Of Studentsmentioning
confidence: 96%
“…Kariuki, Aloka, Gatumu and Gitonga, (2015) adopted Yubero and Navarro (2006) research method and found that boys tend to engage in a wider range of bullying behavior extending from direct physical aggression, to name-calling and threats. However, Kariuki et al (2015) observed that when behavior modification techniques was applied to handle such students, there was a reduction of maladaptive behaviors of the students irrespective of their gender.…”
Section: Figure 1: Conceptual Framework Source: Authors Construct 2019mentioning
confidence: 99%
“…Kariuki, Aloka, Gatumu and Gitonga, (2015) adopted Yubero and Navarro (2006) research method and found that boys tend to engage in a wider range of bullying behavior extending from direct physical aggression, to name-calling and threats. However, Kariuki et al (2015) observed that when behavior modification techniques were applied to handle such students, there was a reduction of maladaptive behaviors of the students irrespective of their gender. Kwaja and Mormah (2011) assessed managing adolescents' maladaptive behaviour in Nigerian Secondary Schools.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…In a study on relationships between perceptions of parental punitive discipline, Kariuki, Akola and Ciriaka (2015) argued that use of disciplinary and forceful measures to enforce proper behavior triggers anger, resentment and deceit which weaken healthy parent child relationship. In concurrence, Anne-Lise (2016) indicated that preschool children with authoritarian parents are withdrawn and unhappy, appear anxious and insecure with peers and react bitterly when frustrated.…”
Section: Communication Social Withdrawal and Learner Participationmentioning
confidence: 99%